Saturday

February 28, 2015

February 28, 2015

Posted by **Sella** on Monday, August 27, 2012 at 9:37am.

1.) 2x/2x^2+5x-3 + 5/x^2-9 =

2.) x-3/12x^3-18x^2 - x+1/16x^2-24x =

3.) 2x/x^2-2x-15 - x-2/3x^2+9x =

- algebra -
**drwls**, Monday, August 27, 2012 at 9:51amUse parentheses to isolate numerators and denominators. For example,

3.) 2x/(x^2-2x-15) - (x-2)/(3x^2+9x)

= 2x/[(x-5)(x+3)] + (x-2)/[3x(x+3)]

= [1/(x+3)][2x/(x-5) + (x-2)/(3x)]

- algebra -
**crissa**, Monday, September 24, 2012 at 8:37am2/a-b+3/a+b

**Answer this Question**

**Related Questions**

calculus - i need to find the derivative using chain rule: (x^2 + 2x - 6)^2 (1-x...

math - sums and differences of a rational algebraic expression 3/a + 2/ab + 1/...

algebra - -12X^6+24x^5-18x^2/-6x^2=2x^4+24x^3-3x could some one check this for ...

Algebra - checking problem Use FOIL to multiply: (6x – 1)(3x – 4) 6x*3x + 6x*(-4...

algebra - 24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3...

algebra - reduce the fraction 6x/12x to lowest terms

algebra - reduce the fraction 6x/12x to lowest terms.

algebra - -12x^6+24x^5-18x^2/-6x^2 3x^4+x^3-3x check see if I did it right.

Math - (2x-1)(3x-7)(4x+3) =6x^2-14x-33x+7 =(6x^2-19x+7)(4x+3) =24x^3+18x^2-126x+...

math - -12x^6+24x^5-18x^2/-6x^2= -4x^8+4x^7-3x tell me if this right